The Eternals Become Eternals Parodying of Jack Kirby’s The Eternals Comic in Chloe Zhao Eternals Movie - S. Filemon Vandits Sidupa; Muarifuddin Muarifuddin; Rahmawati Azi (English Literature Study Program, Faculty of Humanities, Universitas Halu Oleo, 2024)
Parody is one of the intertextual artistic statements with a certain character that has been recognized for a long time not only for witty satire but also for criticism. The object of this research was the Eternals movie (2021) and the Eternals comic(1967-1977). Using a qualitative method, this research is intended to identify the parody. There are two main sources of data collection: film and comic. Then, a series of data collection consists of watching films and taking scenes, dialog, and film visuals, juxtaposing the comic data taken using the reading method, and recording the results of the data found. This study uses Linda Hutcheon's theory of political parody. The result shows that (1) there are forms of parody in the Eternals film, which are described from two perspectives, namely the existence of subversion and legitimacy in several elements such as character function, character gender, storytelling structure, and cultural dilution. (2) There are parodied representations of God in movies and comics. (3) Parody not only changes but also creates incongruity in the placement of women as superior, the portrayal of superheroes, and the portrayal of villains in movies.